ESG Reporting Using UN Sustainable Development Goals - Wilburn, Kathleen; Wilburn, Ralph (Journal of Strategic Innovation and Sustainability, 2020)
Government interest in disclosure of Environmental, Social, Governance (ESG) goals is pressuring corporations to use a reporting structure, like the Global Reporting Initiative (GRI) reporting framework, whose standards include the United Nations 2030 Sustainable Development Goals (SDGs). These SDGs are global, but each has targets and indicators that can be used by corporation to connect their own strategic goals to the SDGs and then to local stakeholders in the global environment. This paper will analyze information from social responsibility/sustainability reports of eleven multi-national corporations using SDGs to assess how the SDGs are being used in defining their strategic goals and measurements.